2019
DOI: 10.1186/s12199-018-0752-x
|View full text |Cite
|
Sign up to set email alerts
|

Having few remaining teeth is associated with a low nutrient intake and low serum albumin levels in middle-aged and older Japanese individuals: findings from the NIPPON DATA2010

Abstract: BackgroundOral health is thought to be associated with diet quality, and socioeconomic status (SES) affects both oral health and diet. The aim of this study was to investigate the association between the number of teeth and dietary intake as well as nutritional biomarker, considering the subjects’ SES.MethodsWe conducted a cross-sectional analysis of data from 2049 individuals aged ≥ 50 years from the National Integrated Project for Prospective Observation of Non-communicable Disease and its Trends in the Aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 31 publications
6
69
0
Order By: Relevance
“…A steep increase in the loss of teeth with age was also reported by other authors [13,27,28,30]. The tooth loss in adults was associated with chewing problems, lower diet quality, reduced nutrient intake and low serum albumin levels [31,32].…”
Section: Discussionsupporting
confidence: 69%
“…A steep increase in the loss of teeth with age was also reported by other authors [13,27,28,30]. The tooth loss in adults was associated with chewing problems, lower diet quality, reduced nutrient intake and low serum albumin levels [31,32].…”
Section: Discussionsupporting
confidence: 69%
“…PD-L1 expression is associated with a 90% excess risk in death for OS and an elevated risk of death among males (Hazard ratio: 1.25) [ 39 ]. In vitro and in vivo studies have shown that PD-1 blockade enhances cisplatin effectiveness and may improve outcomes in humans [ 40 , 41 ]. There is much debate in the literature on sex differences in immunotherapy response with males having better outcomes than females.…”
Section: Discussionmentioning
confidence: 99%
“…In the paper by Nakamura et al [7], the trend for individuals with fewer remaining teeth to have worse nutrient intake was more pronounced among those with low SES. This finding suggests that SES may be intimately involved in the pathway leading from tooth loss to poor nutrient intake.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al [7] studied the relationship between number of teeth and nutrient intake by evaluating not only nutrient intake status obtained from a household-based dietary survey, but also serum albumin level as a nutritional biomarker. They investigated the relationship between number of teeth and nutrient intake by analyzing data from 2049 individuals ≥ 50 years old obtained from the NIPPON DATA 2010 survey.…”
Section: Strengths and Potential Areas Of Considerationmentioning
confidence: 99%